The impact of carbon dioxide (co2) enrichment on rice (Oryza sativa l.) production: a review - Salihi, Mohammad Sadiq; Ahmad Hamdani, Muhammad Saiful; Jusoh, Mashitah (Pakistan Botanical Society, 2022)
Rice (Oryza sativa L.) is one of the world's most important crops and the primary source of calories for more than three billion people worldwide, especially in Asia. Currently, atmospheric carbon dioxide (CO2) concentration is 416 µmol mol-1 and increasing rapidly due to industrialization, which is the main cause of global warming. Current climate change and rising CO2 concentration in the atmosphere have varying global impacts on crop performance. As CO2 is one of the limiting factors in photosynthesis, adding this gas can increase carboxylation activity, hence increasing productivity and yield. Elevated CO2 (eCO2) significantly impacted C3 crops' productivity by increasing photosynthesis, biomass, and grain yield. Plants cultivated under eCO2 conditions demonstrated better development and photosynthesis, lower transpiration, improved water efficiency, decreased inorganic nutrition concentration, increased plant hormone, and compact stomatal density than the plants grown under ambient CO2 (aCO2) conditions. This review discusses the effects of eCO2 on rice plant photosynthesis and growth. The review also describes that eCO2 increased yield components of rice plants. Finally, the current review emphasizes the grain quality of rice that was negatively affected by eCO2. The review paper aims to describe rice production under CO2 increases under climate changes in the future. The synthesis of all this information is helpful to the researchers, advisors of rice farmers, and policymakers to provide a favourable plan by using eCO2 to increase rice plant growth and yield and maintain grain quality through enriching free-air CO2 enrichment (FACE) system for the rice plant to produce enough, and high-quality food for the increasing population of the world.